EXPLORING BPJS CLAIM CHALLENGES IN HOSPITALS AND THEIR IMPROVEMENT STRATEGIES: A SYSTEMATIC LITERATURE REVIEW - Paramita; Paramarta, Vip (Jurnal Manajemen dan Bisnis, 2026)
Delays in BPJS claims remain a significant issue for many hospitals because they can slow the disbursement of funds and disrupt service continuity. This study aims to identify the barriers that cause BPJS claim delays and to formulate appropriate improvement recommendations using a systematic literature review approach. The Systematic Literature Review (SLR) was conducted by searching Google Scholar and Garuda, followed by screening of titles, abstracts, full texts, and quality assessment. From 326 initial articles, 17 studies met the inclusion criteria and were analyzed using thematic synthesis. The review identified five main categories of problems: inaccuracies in diagnosis and procedure coding, incomplete medical records, administrative and internal verification obstacles, limited use of the Hospital Information System (SIMRS), and frequent BPJS policy changes. These findings show that claim delays arise from multidimensional factors related to documentation quality, human resource competence, workflow accuracy, and information system support. The study concludes that improving coder skills, strengthening medical record audits, standardizing SOPs, optimizing SIMRS, and enhancing inter-unit coordination are necessary. The implications provide a scientific basis for developing better claim management strategies to help hospitals accelerate reimbursement processes.